Chicano roots go deep - Coy, Harold (New York : Dodd, Mead, 1975)
Traces the history of the Chicanos in the United States and discusses their general and individual influences on and problems living in an Anglo culture.
Includes index.
Bibliography: p. 199-205.
Keywords: Mexican Americans -- Juvenile literature; Mexican Americans